THE EFFECT OF ORGANIZATIONAL CULTURE TO EMPLOYEES PERFORMANCE AT PT. HERO SUPERMARKET Tbk GIANT MTC PANAM PEKANBARU - Harwina, Yulia (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This research was conducted at PT. Hero Supermarket Tbk Giant Mtc Panam Pekanbaru. The purpose of this study is to determine the effect of orgaisasi culture on employee performance PT. Hero Supermarket Tbk Giant Mtc Panam Pekanbaru. Population in this research is all employees of PT. Hero Supermarket Tbk Giant Mtc Panam Pekanbaru which amounted to 77 people. While the sampling technique is determined by census of 76 people because 1 person is a researcher. Data analysis is done by using validity test, reliability, normality test, simple linear regression, t test and R2 test. The test is conducted to determine the relationship between independent variables (independent variable) with dependent variable (dependent variable). Based on the results of research that the organizational culture affect the employee's performance can be seen from t arithmetic 4.842> t table 1.992 so Ho rejected and Ha accepted. Then the calculation of coefficient of determination (R Square) of = 0,241 (24,1%), it shows that orgaisasi culture influence employee performance equal to 24,1% and the rest 75,9% influenced by other variable not examined in this research . Then the linear regression equation as follows: Y = 26.186 + 0.359X. Thus it can be concluded that the cultural variables orgaisasi (X) affect the performance variable (Y) at PT. Hero Supermarket Tbk Giant Mtc Panam Pekanbaru